Finishing Barn Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D.; Dritz, Steve S.; DeRouchey, Joel; Tonsor, Glynn T. (My University, 2014)
This publication provides estimated cost and returns for a finishing barn.
MF2152_2014_04
Keywords: MF2152; Livestock; Economics; MF